How Do Pre-Service Language Teachers Perform in Mathematical Literacy? A Study at the Tertiary Level - Akmal, Nurul; Marhami, Marhami; Idris, Khairiani; Harun, Jamilah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Mathematical literacy is increasingly recognized as a critical competency for all university students, including those in non-STEM disciplines. However, language education students are often overlooked in discussions surrounding mathematical reasoning. This study examines the mathematical literacy performance of tertiary-level students enrolled in Arabic, Indonesian, and English language education programs. Using a quantitative descriptive design, data were collected from 91 students through assessments covering linear equations, inequalities, graphing functions, and quadratic equations. The study employed one-way ANOVA and Kruskal–Wallis tests to analyze differences in performance. While overall scores did not differ significantly across majors, notable differences were observed in component-level indicators, particularly in Employ and Interpret processes. Indonesian Language Education students demonstrated stronger skills in problem formulation and procedural application, while Arabic Language Education students excelled in interpreting mathematical results. In contrast, English Language Education students showed high procedural ability but struggled with interpretation. These findings highlight uneven cognitive development in mathematical reasoning across programs and underscore the need for integrating numeracy into language education curricula. Recommendations include differentiated instructional strategies, cross-disciplinary teacher training, and policy support to promote holistic and interdisciplinary competencies among future educators.